2014
DOI: 10.1002/eej.22590
|View full text |Cite
|
Sign up to set email alerts
|

Development and Operational Status of Wind Power Forecasting System

Abstract: SUMMARY Itochu Techno‐Solutions Corporation (CTC) and Tohoku Electric Power Co., Inc. have developed a system which predicts the wind power output in the control area of an electric power system in order to contribute to demand and supply control of the power system. Official operation of the system has been started after experimental operation during 3 years. Currently, the forecast information is used as reference information for electric power system operation in Tohoku Electric Power Co., Inc. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Step 5: Carry out a consistency examination to test for the comparison consistency. The value of ξ can be obtained after solving Equation (6). Then, we can test for the comparison consistency through calculating the consistency ratio.…”
Section: The Bwmmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 5: Carry out a consistency examination to test for the comparison consistency. The value of ξ can be obtained after solving Equation (6). Then, we can test for the comparison consistency through calculating the consistency ratio.…”
Section: The Bwmmentioning
confidence: 99%
“…In accordance with the comprehensive evaluation results, the Li-ion battery is the optimal battery ESS to apply to wind-photovoltaic-energy storage combination exemplary projects. Based on the discussion on the comprehensive evaluation results, policy implications are suggested to improve the applicability of battery ESSs and provide some references for decision makers in related fields.Energies 2018, 11, 2841 2 of 26 technically mature electricity generation patterns [6][7][8], it can be impacted by lots of uncontrollable factors, including humidity, temperature, and wind speed. Therefore, wind power generation can be intermittent and fluctuating.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage, we can distinguish Chaves and Terry Bahill (2014), who wanted to know the individual motives that lead to responsible behavior with the environment. Authors such as Aoki, Tanikawa, et al (2014) indicated that in Western countries, a change was taking place in the vision of the world, moving towards what they called the "New Environmental Paradigm", which was concerned with aspects of environmental aesthetics and energy saving. Other…”
Section: Concern For the Environmentmentioning
confidence: 99%
“…From the ancient pyramids of Egypt or the monumental buildings of ancient Rome or ancient Greece to today's complex technological platforms, projects have always existed. They were passing through the construction of the first skyscrapers, railway networks or aircraft of the 20th century, which have involved day after day the improvement and refinement of the different techniques, theories and skills of project management and the application within organizations (Aoki et al 2014).…”
Section: Introductionmentioning
confidence: 99%